Customer Satisfaction Mediates the Effect of Self Service Technology on Customer Loyalty in of Islamic Bank E-Banking Services in Indonesia - Tamar Tamaruddin; Achmad Firdaus; Endri Endri (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2020)
The research objective was to analyze: The effect of self-service technology, service quality, reputation, customer value on customer loyalty in e-banking services for Islamic banks in Indonesia through customer satisfaction. The method used is quantitative with path analysis. The data collection technique is a questionnaire. The results of the study are as follows: 1. There is no direct effect of self-service technology on customer satisfaction in E-Banking services. 2. There is no direct effect of service quality on customer satisfaction in E-Banking services. 3. There is a direct effect of reputation on customer satisfaction in E-Banking services. 4. There is a direct effect of customer value on customer satisfaction in E-Banking services. 5. There is a direct effect of customer satisfaction on customer loyalty in e-banking services. 6. There is no direct effect of self-service technology on customer loyalty in e-banking services. 7. There is a direct effect of customer value on customer loyalty in e-banking services. 8. There is a relationship between self service technology and service quality of Islamic banks. 9. There is a relationship between customer value and reputation of a Sharia bank. 10. There is a significant effect of self-service technology, service quality, reputation, customer value on customer loyalty in Islamic banking e-banking services in Indonesia through customer satisfaction.